Práticas atuais e ideais em intervenção precoce no Alentejo: Perceções dos profissionais - Augusto, H. (2014)
In this study we aim to understand the perceptions that professionals of Local Intervention Teams (LIT) of Alentejo have about their typical practices, as well as their perceptions about the ideal practices. Participants were 167 professionals from 25 teams from Portalegre, Évora, Beja, and the region of the Alentejo coast. Data were collected with the Questionnaire to ECI Professionals and the Portuguese translation of the Families in Natural Environments Scale of Service Evaluation (FINESSE; McWilliam, 2000/2008). According to the results, it appears that (1) there are statistically significant differences between the perceptions that practitioners of LIT of Alentejo have regarding typical and ideal practices; (2) there are no statistically significant differences between the perceptions that professionals of LIT of Alentejo have, in relation to typical and ideal practices, when considering variables such as age, years of experience in ECI, basic training, and further training; and (3) there are statistically significant differences between the perceptions of professionals of LIT of Alentejo regarding typical practices, as a function of professionals perceptions regarding the functioning of their team, with professionals that rate their team as transdisciplinary reporting typical practices closer to recommended practices. The results raise the need to increase transdisciplinarity in LIT as well as the quality of their practices.